Cellular Automata 10th International Conference on Cellular Automata for Research and Industry, ACRI 2012, Santorini Island, Greece, September 24-27, 2012. Proceedings - Sirakoulis, Georgios Ch.; Bandini, Stefania; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Cellular Automata for Research and Industry, ACRI 2012, held in Santorini Island, Greece, in September 2012. The 88 revised papers were carefully selected from numerous submissions. In order to give a perspective in which both theoretical and applicational aspects of cellular automata contribute to the growth of the area, this book mirrors the structure of the conference, grouping the 88 papers into two main parts. The first part collects papers presented as part of the main conference and organized according to six main topics: theoretical results on cellular automata; cellular automata dynamics, control and synchronization; cellular automata and networks; modeling and simulation with cellular automata; cellular automata-based hardware and architectures; codes, pseudorandom number generators and cryptography with cellular automata. The second part of the volume is dedicated to contributions presented during the ACRI 2012 workshops on theoretical advances, specifically asynchronous cellular automata, and challenging application contexts for cellular automata: crowds and CA, traffic and CA, and the satellite Workshop on cellular automata of cancer growth and invasion.
Theoretical results on cellular automata -- Cellular automata dynamics, control and synchronization -- Cellular automata and networks -- Modeling and simulation with cellular automata -- Cellular automata-based hardware and architectures -- Codes, pseudorandom number generators and cryptography with cellular automata -- Crowds and CA -- Traffic and CA -- Cellular automata of cancer growth and invasion.
Keywords: Computer science; Computer Communication Networks; Computer software; Computer simulation; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Simulation and Modeling; Computer Communication Networks; Information Systems Applications (incl. Internet).